Leitura e produção de imagens : um processo educativo e cuidativo dos acadêmicos de enfermagem com crianças hospitalizadas - Vanini, Sandra Maria (2010)
This study is part of the Research Line Educational Processes and Language. Its aim was to investigate the contribution of reading and image production for the establishment of an educational process and nursing care of academics with hospitalized children. Of qualitative approach, the subjects of research were fourteen academic nursing Lutheran University of Brazil, campus Carazinho/RS. They worked in hospitals in the north region of Rio Grande do Sul State, where reading and have stimulated the production of images with the aid of an instrument drawn up by the author of the project, titled "When a child is sick!". Data collection was performed through a non-structured interview; the interviews occurred after academics conducting activities with hospitalized children. The data were analysed based on the phenomenological method proposed by Giorgi (2010) and Comiotto (1992).This understanding emerged four essences: drawing in academic-child communication; humanization in health and education; interpersonal relationships in hospital environment; and, personal and professional formation. It was noted that the use of drawing, with children, favored the communication between them and academics; the relationship between hospitalized children and survey provided an indirect careful to parents. Reading and producing images proved as appropriate working instruments in health education and downloads nurture understanding of new forms of teaching. The experience was heartened nursing academics regarding the importance of establishing human relations in their practices with hospitalized children